Exposure to out-group cultural holidays increases intergroup social distance - Lu, Jiahui (2018)
Cultural holidays are culturally themed, public celebrations that are held collectively and regularly in the society. In four studies, we explored the effect of exposure to holidays from out-group cultures on intergroup social distance and investigated the role of salience of one’s nonmembership in the out-group (i.e., negational identity salience) as the cognitive mechanism. Study 1 showed that exposure to outgroup cultural holidays (i.e., Hari Raya Puasa for the Malay, Deepavali for the Indian) was associated with Singaporean Chinese’s increase in linguistic distance in social media updates on Twitter. Study 2 experimentally manipulated exposure to Hari Raya Puasa and found that such exposure caused a decreased self-report willingness for casual interactions with Malay members for Singaporean Chinese. Study 3 showed that such a distancing effect was caused by the exposure to the out-group holiday but not the mere exposure to the out-group. Study 4 further showed that exposure to celebratory activities related to Hari Raya Puasa drove the distancing effects, especially for participants who highly identified with the Chinese culture. Furthermore, negational identity salience mediated such interaction effect on willingness for close interactions with Malay members. Overall, these results demonstrate that exposure to out-group cultural holidays increases social distance from the out-group members in the context of majority groups exposing to cultural holidays of minority groups. The current research extends the understanding of social impacts of cultural holidays on intergroup relations, presents cultural holidays as important contexts for studying intergroup relations in the field, and highlights the critical role of negational identity salience in increasing intergroup social distance.